Stable isotope geochemistry. (6th ed.) - Hoefs, Jochen. (Springer, 2017)
Stable Isotope Geochemistry is an introduction to the use of stable isotopes in the geosciences. It is subdivided into three parts: theoretical and experimental principles; fractionation processes of light and heavy elements; the natural variations of geologically important reservoirs. Since the application of stable isotopes to earth sciences has grown in the last few years, a new edition appears necessary. Recent progress in analysing the rare isotopes of certain elements for instance allow the distinction between mass-dependent and mass-independent fractionations. Special emphasis has been given to the growing field of "e;heavy"e; elements. Many new references have been added, which will enable quick access to recent literature. For students and scientists alike the book will be a primary source of information with regard to how and where stable isotopes can be used to solve geological problems.